Revisiting voltage-coupled H+ secretion in the collecting duct: review - Ayasse, Niklas; Berg, Peder; Sørensen, Mads V.; Svendsen, Samuel L.; Weinstein, Alan M.; Leipziger, Jens (American journal of physiology. Renal physiology, 2024)
Experimental studies have shown that V-type ATPase-driven H+ secretion is dependent on transepithelial voltage. On this basis, the “voltage hypothesis” of urinary acidification by the collecting duct was derived. Accordingly, it has been supposed that the lumen-negative potential created by the reabsorption of Na+ via the epithelial Na+ channel (ENaC) enhances electrogenic H+ secretion via V-type H+-ATPase. This concept continues to be widely used to explain acid/base disorders. Importantly, however, a solid proof of principle for the voltage hypothesis in physiologically relevant situations has not been reached. Rather, it has been challenged by recent in vivo functional studies. In this review, we outline the arguments and experimental observations explaining why voltage-coupled H+ secretion in the collecting duct often appears poorly applicable for rationalizing changes in H+ secretion as a function of more or less ENaC function in the collecting duct.
Im Titel ist das Plus-Symbol bei "H+" hochgestellt
Gesehen am 07.04.2025